Analisis Yuridis dan Humanis Fenomena Pernikahan di Bawah Umur di Tengah Arus Romantisme Media Sosial - Wulan, Nandar; Putri, Sekar Rahayu; Muling, Candra Wijaya (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Underage marriage in Indonesia is currently facing a troubling paradox. On the one hand, the state has demonstrated juridical progressiveness through Law Number 16 of 2019, which tightens the minimum legal age for marriage. On the other hand, the social media ecosystem has instead fostered a trend of romanticizing early marriage through aesthetic content and simplistic narratives of “moral salvation” or “avoiding adultery.” This paper aims to examine this phenomenon using a normative-sociological research method with a legal humanism approach. The critical analysis shows that the instrument of marriage dispensation in the courts often transforms into a legal shortcut that overlooks aspects of psychological maturity, economic readiness, and children’s reproductive rights. The findings conclude that law enforcement will not be effective if it remains merely administrative in nature. An integrative policy redefinition is required, encompassing the harmonization of judicial decision-making standards, the enhancement of digital literacy among Generation Z, and the holistic strengthening of child human rights protection. This paper recommends that the law should no longer act as a “passive spectator” amid the tide of digitalization that reduces the meaning of marriage to mere social media content.